Cyberspace Sovereignty Reflections on building a community of common future in cyberspace - Fang, Binxing (Springer Singapore, 2018)
This book is the first one that comprehensively discusses cyberspace sovereignty in China, reflecting China's clear attitude in the global Internet governance: respecting every nation's right to independently choose a development path, cyber management modes and Internet public policies and to participate in the international cyberspace governance on an equal footing. At present, the concept of cyberspace sovereignty is still very strange to many people, so it needs to be thoroughly analyzed. This book will not only help scientific and technical workers in the field of cyberspace security, law researchers and the public understand the development of cyberspace sovereignty at home and abroad, but also serve as reference basis for the relevant decision-making and management departments in their work.